Respiratory Viral Infections in Multiple Myeloma Patients. (4th October 2017) - Burgess, Mary J; Mohan, Meera; Crescencio, Juan Carlos Rico; Wolfe, Frankie; Bellamy, William; Kothari, Atul
Abstract: Background: Multiple myeloma (MM) patients are at increased risk of respiratory viral infections (RVIs) due to disease-related alterations in their immune systems. Data in the literature specific to MM patients is limited. We reviewed four years of multiplex respiratory viral panel (RVP) data in MM patients at our institution to evaluate incidence and seasonality of RVIs. methods. The results from all positive RVPs, obtained via nasopharyngeal swab and as identified by polymerase chain reaction during the years 2013 to 2016, were analyzed. A positive result less than 6 weeks apart was considered a duplicate and removed. All specimens were analyzed in the molecular diagnostics laboratory using the eSensor® Respiratory Viral Panel (GenMark Dx, Carlsbad, CA). This assay is a qualitative nucleic acid multiplex in vitro diagnostic test that provides for the simultaneous detection and identification of 14 respiratory viral nucleic acids. Results. RVIs were reported in every month in all four years. The peak months were January and February, driven by the peak activity of Influenza and respiratory syncytial virus (RSV). Rhinovirus was isolated the most frequently. The least isolated was Adenovirus. A seasonality was observed with Influenza, RSV, human parainfluenza and human metapneumovirus; however, infections with each virus occurred outside of peak months including an outbreak of Influenza in July and August 2013. The total number of viral infections varied each year as did the total number for each virus. The year 2015 had the lowest number of RVIs reported at 427, followed by the year 2016 with the most RVIs reported at 515. However, 2016 was not the peak incidence for each virus; it was the peak incidence for RSV and Rhinovirus. In fact, Influenza had its lowest number of cases in 2016. Conclusion. At our institution, we have shown that RVIs are more common than previously described in MM patients. RVIs occur in every month throughout the year. Although a seasonality is seen with these viral infections, infections do occur outside of the months considered to be peak months for each virus. Infection control policies, therefore, must be enforced year round. More studies, however, are needed to assess the proportion of community vs. healthcare acquired. Two Disclosures: All authors: No reported disclosures.